AN ANALYSIS ON SHORT-WAVE COMPONENTS OF THE GLOBAL STRESS FIELD - Huang X.; Wei D.; Chen Q.; Chen H. (My University, 2003)
The 10 920 stress indicators collected so far by the WSM (World Stress Map) project represent the observed orientations of the maximum horizontal principal stress (σ Hmax) in a certain region. Assuming that the long-wave component of σ Hmax is expressed by the absolute direction of plate motions, we can get the relative orientation and the magnitude of the short-wave component resulted from the local tectonic process or other factors with vector analytical technique. The global surface was divided into basic element bins by 2.5°×2.5° dimensions and the WSM indicators were statistically analyzed for each element by weight coefficient method in order to determine the mean orientation of the stress. We calculated the long-wave component of the global stress field using HS2-NUVEL1 model. The relative magnitude or the direction limitation of short-wave component, which reflect the local contribution to the observed stresses, was determined by the angle between the mean σ Hmax and the orientation of the long-wave component. The results of this paper show that the contribution of either the long-wave component or the short-wave component is approximately equal to most of the global plates on the basis of the mean effect of the observed stresses. For some of continental regions, the local active tectonics plays an important role in the observed stresses and controls the generation and occurrence of earthquakes.
Keywords: stress field; Euler vector; short-wave component